Optimal placement of distributed generation in electric power system (2009)
This article presents a methodology for the optimal location of distributed generation in electric power systems. Candidate bars to locate distributed generation are identified based on local marginal prices. These prices are obtained by solving an optimal power flow (OPF) and correspond to the Lagrange multipliers of the active power balance equations in each of the system bars. To include distributed generation in the OPF, it has been modeled as a negative injection of active power. The methodology consists of an iterative nonlinear process where distributed generation is located in the bar with the highest marginal price. Three types of distributed generation were considered: 1) internal combustion engines, 2) gas turbines and 3) microturbines. The proposed methodology is evaluated in the 30-bar IEEE system. The results obtained show that distributed generation contributes to the reduction of nodal prices and can help solve congestion problems in the transmission network.